Akurasi dan Nilai-Nilai Aksiologi Penentuan Arah Kiblat pada Mushola UIN Syekh Wasil Kediri Perspektif Ilmu Falak dan Filsafat Etika: Accuracy and Axiological Values in Determining the Qibla Direction at the Mushola of UIN Syekh Wasil Kediri: A Perspective of Islamic Astronomy and Ethical Philosophy - Sheyla Nichlatus Sovia; Muthi'ah Hijriyati (Institut Agama Islam Negeri Fattahul Muluk Papua, 2026)
This study aims to analyze the axiological values underlying Qibla direction determination from the perspectives of Islamic astronomy (ʿilm al-falak) and ethical philosophy. The research employs a descriptive qualitative method with a limited field study and an interdisciplinary approach. Data were collected through literature review, observation, and measurements conducted at several prayer rooms within UIN Syekh Wasil Kediri, including geographic coordinates, Qibla calculations using spherical trigonometry, and verification through GPS, compass measurements, and astronomical applications. The findings reveal that Qibla determination has evolved from classical astronomical methods to the use of modern technologies that enable more accurate measurements. Variations in Qibla direction results are influenced by differences in coordinate data, instrument precision, geographical and environmental conditions, and human error. From an axiological perspective, Qibla accuracy possesses not only technical significance but also reflects values of truth, utility, moral responsibility, and scientific integrity. Ethical principles such as objectivity, methodological verification, data transparency, openness to correction, and epistemic justice are essential for ensuring the validity and accountability of Qibla determination. These findings demonstrate that Qibla direction determination constitutes a scientific practice that integrates astronomical accuracy, ethical responsibility, and spiritual values.